2022
DOI: 10.1002/jbm.a.37372
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of medical device infections via multi‐action nitric oxide and chlorhexidine diacetate releasing medical grade silicone biointerfaces

Abstract: The presence of bacteria and biofilm on medical device surfaces has been linked to serious infections, increased health care costs, and failure of medical devices. Therefore, antimicrobial biointerfaces and medical devices that can thwart microbial attachment and biofilm formation are urgently needed. Both nitric oxide (NO) and chlorhexidine diacetate (CHXD) possess broad-spectrum antibacterial properties. In the past, individual polymer release systems of CHXD and NO donor S-nitroso-Nacetylpenicillamine (SNAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…These results suggested that the SNAP–Si–SR surface became more hydrophobic than the controls and had similar hydrophobicity like SNAP impregnated silicone materials (104–110°) reported in prior literature. 31,68–70…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggested that the SNAP–Si–SR surface became more hydrophobic than the controls and had similar hydrophobicity like SNAP impregnated silicone materials (104–110°) reported in prior literature. 31,68–70…”
Section: Resultsmentioning
confidence: 99%
“…75 Comparable results have been reported in the literature with NO-releasing materials that show decreased bactericidal efficiency against E. coli and other Gram-negative bacteria. 68,76…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface modifications of NO-releasing antibacterial polymer coatings are attempted to bestow additional antibacterial properties to synergistically combat bacteria. These techniques involve incorporation of the NO donor along with secondary antibacterial agents such as nanoparticles, antibiotics, antimicrobial peptides, and other antiseptic molecules . The reported studies usually contain a NO donor incorporated into the base polymer, which is top-coated with a polymer containing secondary active molecules (see Table ).…”
Section: Advancements In Nitric Oxide-releasing Multifunctional Biome...mentioning
confidence: 99%
“…Hence, approaches that involve other clinically available antimicrobial catheter materials have also been combined with NO-releasing properties to create multifunctional medical device interfaces for a greater level of microbial eradication. Recently, a method to modify silicone rubber medical device interfaces to incorporate the NO donor SNAP and the commonly used broad-spectrum antiseptic chlorhexidine (CHXD) was reported . The antiseptic CHXD was top-coated on the SNAP-loaded surface at various concentrations.…”
Section: Advancements In Nitric Oxide-releasing Multifunctional Biome...mentioning
confidence: 99%